2006
DOI: 10.1007/s00421-006-0179-8
|View full text |Cite
|
Sign up to set email alerts
|

Increased expired NO and roles of CO2 and endogenous NO after venous gas embolism in rabbits

Abstract: Venous gas embolism (VGE) is a feared complication in diving, aviation, surgery and trauma. We hypothesized that air emboli in the lung circulation might change expired nitric oxide (FeNO). A single intravenous infusion of air was given (100 mul kg(-1)) to three groups of anaesthetized mechanically ventilated rabbits: (A) one with intact NO production, (B) one with intact NO production and where end-tidal CO(2) was controlled, and (C) one with endogenous NO synthesis blockade (L: -NAME, 30 mg kg(-1)). Air infu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
13
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 28 publications
2
13
0
Order By: Relevance
“…In line with previous reports (Emerson et al. 1999, Agvald et al. 2006), our results indicate that endogenous NO protects against the pulmonary hypertension and the mortality associated with acute pulmonary embolism, although the study by Agvald et al.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…In line with previous reports (Emerson et al. 1999, Agvald et al. 2006), our results indicate that endogenous NO protects against the pulmonary hypertension and the mortality associated with acute pulmonary embolism, although the study by Agvald et al.…”
Section: Discussionsupporting
confidence: 94%
“…Whereas endogenous NO production protects against the mortality associated with pulmonary embolization (Emerson et al. 1999, Agvald et al. 2006), we found that iNOS‐derived NO produces unfavourable effects.…”
mentioning
confidence: 63%
See 1 more Smart Citation
“…111 A study in rabbits suggests that any hope of a favorable physiological response to VAE requires an intact endogenous production of nitric oxide, as blockade of this system resulted in universal fatalities. 112 In dogs, antagonism of endothelin-1, a vasoactive mediator released after pulmonary embolism, attenuated both the decrease in mean arterial pressure and the increase in pulmonary vascular resistance seen after VAE. 87 Anecdotally, inhaled epoprostenol has been used successfully after carbon dioxide embolism, resulting in prompt normalization of PAP.…”
Section: Supportive Measures and Oxygen Therapymentioning
confidence: 99%
“…NO is a vasodilator in the pulmonary circulation 4 and we found that the fraction of NO in exhaled gas (FENO) increased in acute PE and that endogenous NO production was protective in two models of experimental PE. 5,6 The NO donors nitroglycerin and sodium nitroprusside have shown some beneficial effects in animal models of PE, but the vasodilation was more pronounced in the systemic circulation and nitroglycerin may also impair the gas exchange, thereby limiting the applicability of these drugs in acute PE. 7,8 Furthermore, sildenafil, inorganic nitrite and a nitric oxide-releasing aspirin have shown beneficial effects in animal models of acute PE.…”
Section: Introductionmentioning
confidence: 99%